2016
DOI: 10.1097/rct.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Computed Tomography Virtual Monoenergetic Imaging of Lung Cancer

Abstract: Virtual monoenergetic imaging reconstructions at 60-keV provided the best combination of subjective and objective image qualities in DECT of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
17
1
3
Order By: Relevance
“…In addition, DECT‐based VMIs can be used to assess fatty liver and hypervascularized abdominal tumors . Despite promising results obtained in recent investigations, the noise levels of DECT‐based VMIs were high at low and high keVs …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, DECT‐based VMIs can be used to assess fatty liver and hypervascularized abdominal tumors . Despite promising results obtained in recent investigations, the noise levels of DECT‐based VMIs were high at low and high keVs …”
Section: Introductionmentioning
confidence: 98%
“…In particular, virtual monoenergetic images (VMIs) derived from DECT images have shown encouraging results and gained popularity recently . Clinical applications of DECT‐based VMIs include metal artifact reduction, beam‐hardening correction, contrast and noise optimization, and material differentiation . In addition, DECT‐based VMIs can be used to assess fatty liver and hypervascularized abdominal tumors .…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee the clinical feasibility and safety of proton treatment planning on MonoCTs instead of SECT scans, specific requirements have to be fulfilled, which were evaluated within this study: similar image quality, at least comparable precision in range prediction, and no clinically relevant changes in dose distributions. This stepwise clinical implementation already provides with MonoCTs more possibilities to increase tissue contrast (14)(15)(16)(17)(18) and to reduce metal artifacts (13,19), and it offers the opportunity to determine the ultimate role of DECT in proton therapy in a subsequent step by quantifying the potential benefits of a patient-specific DECT-based proton range prediction on a large DECT tumor patient database.…”
Section: Introductionmentioning
confidence: 99%
“…9 Kaup et al found the optimal MEI energy level for subjective and objective image quality of lung cancer lesions. 10 11,12 Furthermore, it has been shown that enhancements in CT image quality reduce uncertainties in patient positioning during image-guided radiation therapy (IGRT) and hence can reduce setup margins during treatment planning. 13 It follows that contrast enhancement from DECT would improve the quality of IGRT planning and delivery.…”
Section: B Applicationsmentioning
confidence: 99%
“…The following year Sudarski et al evaluated subjective and objective image quality enhancements for MEI of gastrointestinal stromal tumors . Kaup et al found the optimal MEI energy level for subjective and objective image quality of lung cancer lesions . Two studies (Frellessen et al and Hardie et al) demonstrated a contrast enhancement for diagnostic pancreatic imaging .…”
Section: Introductionmentioning
confidence: 99%